Perspectives on climate change in medical school curricula-A survey of U.S. medical students - Karly Hampshire; Allan Ndovu; Hriday Bhambhvani; Nicholas Iverson, MD (Elsevier, 2021)
Introduction: Although climate change has been identified as one of the greatest threats to health, medical school curricula have very little coverage of its health consequences. While students are key stakeholders in medical school curricula, their perspectives on the inclusion of this content are largely unknown. This study sought to evaluate medical student perceptions on the intersection of climate change and health in medical education. Materials and methods: Authors surveyed students at select U.S. medical schools from April-July 2020 using Likert-scale items, multiple choice questions, and free text responses. Data was analyzed using descriptive statistics, and a regression analysis was performed to assess student characteristics predictive of stronger beliefs in climate health education. Results: Of 600 student respondents at 12 medical schools, 83.9% (n=503) believed that climate change and its health effects should be included in the core medical school curriculum, but just 13.0% (n=78) believed that their school currently provides adequate education. Only 6.3% of students (n=38) felt they would be "very prepared" to discuss the question, "How can climate change affect my health?" with a patient. There was no significant association between student beliefs regarding climate change in medical education and age, medical school region or rank, or stage of training, though students with no or low past or present engagement with climate change had significantly lower scores in a composite score assessing belief in climate change's health effects and place in medical education. Discussion: The majority of medical students believe that climate change should be a core topic in medical school curricula and current coverage is inadequate. By demonstrating student demand to fill this educational gap, this study functions as a needs assessment in the development of climate health curricula moving forward.